Community Health Worker Initiatives: An Approach to Design and Measurement. Issue 2 (1st March 2022) - Jayapaul-Philip, Bina; Shantharam, Sharada S.; Moeti, Refilwe; Kumar, Gayathri S.; Barbero, Colleen; Rohan, Elizabeth A.; Mensa-Wilmot, Yvonne; Soler, Robin
Abstract : Context: The Centers for Disease Control and Prevention supports the engagement of community health workers (CHWs) to help vulnerable populations achieve optimum health through a variety of initiatives implemented in several organizational units. Program: This article provides a unified and comprehensive logic model for these initiatives that also serves as a common framework for monitoring and evaluation. Implementation: We developed a logic model to fully describe the levels of effort needed to effectively and sustainably engage CHWs. We mapped monitoring and evaluation metrics currently used by federally funded organizations to the logic model to assess the extent to which measurement and evaluation are aligned to programmatic efforts. Evaluation: We found that the largest proportion of monitoring and evaluation metrics (61%) currently used maps to the "CHW intervention level" of the logic model, a smaller proportion (37%) maps to the "health system and community organizational level, " and a minimal proportion (3%) to the "statewide infrastructure level." Discussion: Organizations engaging CHWs can use the logic model to guide the design as well as performance measurement and evaluation of their CHW initiatives.